Exploring a secondary urban ESL program: addressing the social, affective, linguistic, and academic needs of English language learners (ELLs) - Lundien, Katrina (Kansas State University, 2009)
Offering a high-quality education to English language learners (ELLs) is a challenge in schools across the United States. Yet, few studies have been conducted to investigate high school English as a second language (ESL) programs. This study provides insights into how a Kansas urban high school ESL program promotes access to the curriculum for ELLs by providing for their social, affective, linguistic, and academic needs. The purpose of this dissertation is to use the premise of educational equity and Catherine Walsh’s (1991) educational needs for ELL school success to explore how structural components of the ESL program in this study promote the access of ELLs to the curriculum. This study offers (1) insights into how urban school districts with high ELL populations might address the issue of access to the curriculum, (2) insights into various perceptions of participant groups—administrators, teachers, and students, and (3) insights into how ESL program components address the educational needs for ELLs to gain access to the curriculum. More specifically, this study emphasizes the following four structural components of the ESL program: (1) student placement, (2) sheltered content courses, (3) teaming, and (4) Spanish for native speakers courses. These structural components are used as a lens to view how social, affective, linguistic, and academic needs of ELLs are addressed. Although the results of this study cannot be generalized to other schools or districts, this study may help other districts, schools, and individual teachers make informed decisions. By demonstrating how four structural ESL program components meet the needs of ELLs in a high school setting, other educators might replicate components on their journey for educational equity within their own venues.
Keywords: ESL secondary programs; High school ESL; ESL curriculum access; English language learners' needs; ESL program evaluation; Equal educational opportunity for ELLs; Education, Bilingual and Multicultural (0282); Education, Secondary (0533); Education, Teacher Training (0530)